Informal Employment and Worker's Well-Being in the Russian Federation - Kim, Yeon Soo; Matytsin, Mikhail; Freije, Samuel (World Bank, Washington, DC, 2019)
This paper finds that informal workers are more likely to have inferior work conditions, but do not necessarily report worse subjective well-being. Starting with lower wages, but also with less regularity of hours and paid vacation, informal workers have higher incidence of envelope payments than formal workers but not of hazardous or unstable jobs. After controlling for work conditions, informal workers do not have statistically significantly lower job satisfaction and under no specification are informal workers more likely to self-assess worse health than formal workers. Finally, there is some association between informal employment and household poverty and life satisfaction, but it is not robust to changes in econometric specification or sample composition. The authors conclude that the evidence indicates that informal employment in the Russian Federation is mostly a problem of labor productivity and the design of the social protection system, but worsening wages and some association between informality and household poverty indicate that informality may also be a social equity problem.